Effects of Ground Transport in Kemp's Ridley (Lepidochelys kempii) and Loggerhead (Caretta caretta) Turtles. Issue 1 (19th May 2020) - Hunt, K E; Merigo, C; Burgess, E A; Buck, C Loren; Davis, D; Kennedy, A; Lory, L; Wocial, J; McNally, K; Innis, C
Synopsis: Many juvenile Kemp's ridley ( Lepidochelys kempii ) and loggerhead ( Caretta caretta ) turtles strand during fall on the beaches of Cape Cod (MA, USA), with total stranding numbers sometimes exceeding 300 turtles per year. Once rehabilitated, turtles must be released at beaches with appropriate water temperatures, often requiring transportation to southeastern coastal states of the USA. These transportation events (transports) may approach or exceed 24 h in duration. Kemp's ridley turtles are known to exhibit an adrenal stress response during such transports, but the effect of transport duration has been unclear, and no other sea turtle species has been investigated. To assess whether transport duration and/or species affects physiological reactions to transport, we studied pre- and post-transport physiological measures in Kemp's ridley and loggerhead turtles transported by ground for <6, ∼12, ∼18, or ∼24 h, comparing with matched "control events" in which turtles were studied without transport. Blood samples were analyzed for four stress-associated measures (corticosterone, glucose, total white blood cell [WBC] count, and heterophil/lymphocyte ratio [H/L]) and nine measures of clinical status (pH, pO2, pCO2, HCO3, sodium, potassium, ionized calcium, lactate, and hematocrit). In both species, stress-associated measures elevated significantly during transport, while handling without transport had no significant effects. Loggerheads exhibited a greater stress response than Kemp's ridleys across all transport durations. These results indicate that sea turtles do react physiologically to ground transport; therefore, minimizing transport time and streamlining transport logistics (where feasible) may help ensure release of rehabilitated turtles to sea in the best possible condition. Nonetheless, both species remained in good clinical condition even after 24 h transport, indicating that current transport protocols are generally safe for sea turtles from a clinical perspective.